EVALUATING CONTINUOUS REVIEW AND PERIODIC REVIEW SYSTEMS FOR BOTTLED WATER RAW MATERIAL INVENTORY MANAGEMENT - Syahidah Amaturrosyid; Rudi Nurdiansyah; Abdul Muid; Aisyah Larasati; Sevira Nallendra Putri; Shafa Wulan Ramadhanti; Virna Rachma Fitriani (RADJA PUBLIKA, 2026)
Intuition-based inventory planning at PT XYZ, a brand-owning bottled water company, has led to inventory imbalances resulting in overstocking and stockouts that trigger cost inefficiencies. This study aims to perform a comparative analysis between the company's actual policy, the Continuous Review System (Q-System), and the Periodic Review System (P-System) methods to optimize inventory costs. The research utilizes a quantitative comparative approach on 330 mL and 600 mL variants using 2025 operational data. The results indicate that the Q-System can reduce operational costs by up to 33,62%, while the P-System only yields marginal cost savings of 4,04% compared to the actual method. For both the 330 mL and 600 mL variants, the Q-System proved to be the definitively superior model by maintaining a much smaller, yet highly secure safety stock. In conclusion, the company is advised to fully transition its inventory policy to the Q-System to minimize physical holding costs while effectively eliminating the expensive risk of stockouts in a volatile market.